Spontaneous rupture of the esophagus: Death caused by massive hemorrhage - Brandolino, Mario; Martínez, José L; Chifflet, Juan; Bertullo, Hugo; Carraro, Carlos (Cirugía del Uruguay, 1984)
Death caused by massive hemorrhage. Description of a case of spontaneous rupture of the esophagus, causing death by massive hemorrhage, as a consequence of ulceration of the thoracic aorta re• sulting from decubitus ulcer originated by a drainage tube.